Training on food safety epidemiology - Deka, Ram P. (International Livestock Research Institute, 2023)
A collaborative project between the International Livestock Research Institute (ILRI) and the Indian Veterinary Research Institute (IVRI) was initiated under the One Health Initiative during May 2023. Launched at IVRI, Bareilly, Uttar Pradesh, this joint project seeks to implement targeted activities related to food safety. As a significant component of this initiative, the three-day ILRI-IVRI joint training on 'Food Safety Epidemiology' was conducted from December 11-13, 2023. This training aimed at capacity building of the project team and faculty at IVRI to address the multifaceted challenges associated with disease emergence, particularly in the context of increased human-animal interactions within the poultry value chain.